Political Discourses Around the Single Union Law and Conceptions about the Organisation of the World of Labour: From Historical to Current Dilemmas - Amaral, Virgílio (2015)
5th International Conference on Humanities and Social Sciences, 25-26 September, 2015, Rome, Italy